Use of recombinant human parvovirus B19 antigens in serological assays. Issue 9 (September 1993) - Cubie, H A; Leslie, E E; Smith, S; O'Neill, H J; Hart, H; Cohen, B J; Inglis, J M
Abstract : AIMS–To compare the sensitivity, specificity, and practicality of recombinant proteins in serological tests for the detection of human parvovirus B19 IgG and IgM. METHODS–Indirect enzyme linked immunosorbent assays using B19 structural proteins expressed in Escherichia coli were developed for the detection of B19 specific IgG and IgM (rELISA-G and rELISA-M). Cells infected with baculovirus expressing B19 structural proteins were also used in an indirect immunofluorescence assay for IgG and IgM antibodies (IFA-G and IFA-M). Antibody capture radioimmunoassays for IgG and IgM (GACRIA and MACRIA) were used as comparative assays. RESULTS–Twenty nine pools of intravenous immunoglobulin were clearly positive for B19 IgG by rELISA-G and contained low IgG titres by GACRIA. From 113 samples tested by all methods, sensitivities of 92% (77/84) and 97% (68/70) were obtained for ELISA and immunofluorescence, respectively, when compared with GACRIA. One hundred and sixteen samples from patients presenting with rash or arthralgia were compared by MACRIA, rELISA-M, and IFA-M. Sensitivities of both recombinant tests were more than 95%. Despite pretreatment to remove IgG or rheumatoid factor, false positive results were a problem in the rELISA-M but were not seen with the IFA-M. CONCLUSIONS–The limited supply of native antigen has severely restricted the wide application of serology for parvovirus B19. The use of recombinant antigens permitted the introduction of local screening tests which had many advantages, including quicker results and relief of the burden on the Reference Laboratory. The use of rELISA-M for sensitivity and IFA-M for specificity and confirmation proved a useful and practical combination for diagnosis of recent infection with B19, and rELISA-G allowed the immune response to be determined in selected populations.